MASAK MINYAK RITUAL IN LO CIA BIO TEMPLE - Nadia Friska Irawan Siregar (Bambuti, 2023)
Abstract This article describes the ritual of Masak Minyak as a traditional medicine at the Lo Cia Bio temple. This healing ritual is held during the birthhday ceremony of Lo Cia/Ne Zha as the host deity of this temple. The research methodology and data collection technique used is a qualitative method, in the form of collecting data by direct interviews and field observations. Field observations were carried out during the ceremony of Lo Cia’s birthday from 10th October to 14 th October 2021 with a descriptive analysis design. The aim of this study is to describe the preparations for the Lo Cia’s birthday ceremony, as well as to explain the ritual of Masak Minyak as a traditional medicine at the Lo Cia Bio Temple.The results of the study show that the Lo Cia’s birthday ceremony is a form of cult and pray to Lo Cia and the ritual Masak Minyak is a form of pray as a Chinese traditional medicine in that ceremony.